(untitled) (Revista Inclusiones, 2021)
The aim of this paper is to explore the country-specific causes of mental health risk alerts (MHRA) and loneliness during the pandemic among populations aged 60+ in three Balkan countries: Bulgaria, Romania and Greece. Persons 60+ years of age are a high-risk group from a health (infection severity) and social (physical distance, self-isolation) perspective due to Covid-19. The lockdown measures in force differ between countries and have highlighted the importance of intensive social contacts and family support. Lack of social contact, anxiety and loneliness increase the risks for mental health, and analysis reveals interesting comparative insights. Restriction of physical contact and fear of infection intensify feelings of anxiety and loneliness, but there is insufficient empirical evidence on how these factors affect the 60+ age group in the three Balkan countries. The analysis is based on the SHARE Corona survey, with pre-selection of panel members 60+ years of age. Anxiety, depression, and loneliness also depend on social networks. In addition, low socioeconomic status is associated with a higher risk of mental disorders, especially during the outbreak, due to general economic uncertainty. There are peculiarities across the countries in terms of sociodemographic characteristics of the 60+ population, as well as self-assessment of household economic status since the beginning of the pandemic. The degree of MHRA and loneliness varies between countries and corresponds to the severity of the anti-epidemic measures introduced. Participation in social networks during the pandemic also varies between countries and various sociodemographic groups. The results of the logistics models support the hypothesis that factors influencing the increased MHRA and loneliness are country-specific. The outbreak and its influence on the population must be analysed within a specific national context. Anti-epidemic measures and the severity of the pandemic differ between countries, and MHRA and loneliness depend on national and cultural specifics.